Densidade populacional e época de plantio no crescimento e produtividade da couve-flor cv. verona 284 - de Queirós Pôrto, Diego Resende; Filho, Arthur Bernardes Cecílio [UNESP]; Rezende, Bráulio Luciano Alves; Barros Jr., Aurélio Paes; da Silva, Gilson Silvério [UNESP] (My University, 2012)
To study plant growth and yield of cauliflower, two field trials were carried out: the first springsummer (Oct. 07, 2006 to Jan. 28, 2007) and the second autumn-winter (Apr. 04, 2007 to Jul. 09, 2007). The experimental design was randomized complete blocks in 4 × 4 factorial design with three replications. The following factors: line spacing (0.6, 0.8, 1.0 and 1.2 m) and plant spacing (0.4, 0.5, 0.6 and 0.7 m). The used cultivar was cv. Verona 284. The characteristics, number of leaves by plant, diameter of stem, diameter of inflorescence, inflorescence mass and yield were evaluated. With the reduction in spacing, were observed lower numbers of leaves, stem diameter, diameter and mass of the inflorescence, but there was an increase in yield. The maximum yield (23 t ha-1) was obtained with 0.6 × 0.4 m, ie, in higher plant population (41,667, plants ha-1).
Population density and planting time on the growth and yield of cauliflower Cv. verona 284
Keywords: Botrytis; Brassica oleracea var; Line spacing; Plant spacing; Production